Recent Developments from Experiments on HMX Reactions - Morley, Olivia (Cranfield University, 2020)
When studying the visible emission of light in the deflagration of energetic materials, two main features are present. Firstly, continuous blackbody radiation across the visible range, which can be used to calculate the temperature of the reaction, by a well-known method using Planck’s formula. Using two different initiation methods of HMX resulted in different temperatures being measured from this radiation, hinting that the reaction pathway is dependent on the initiation insult. The other optical feature that appears are spectral peaks, with light emission at a specific energy/wavelength from particles present in the reacting material. The most intense of these spectral peaks belongs to sodium impurities, which are both prevalent and have a high enough emissivity to dominate over other emissions. Under the high pressures of deflagration, the location of the sodium peak is red-shifted, and found to have a dependence on the pressure (P) and temperature (T). The red-shift was measured under a range of pressures to have a dependence equal to (950 ± 30) PT-0.7 nm, allowing pressure to be measured based on sodium impurity peaks present in the visible emission of deflagration, producing a non-intrusive fast measurement at the point of reaction.
Keywords: 'DSDS20 Poster'; 'DSDS20'; 'Deflagration'; 'Optical spectroscopy'; 'HMX'; 'Catalysis and Mechanisms of Reactions'